A Generic LC-HRMS Screening Method for Marine and Freshwater Phycotoxins in Fish, Shellfish, Water, and Supplements - Mirjam D. Klijnstra (MDPI AG, 2021)
Phycotoxins occur in various marine and freshwater environments, and can accumulate in edible species such as fish, crabs, and shellfish. Human exposure to these toxins can take place, for instance, through consumption of contaminated species or supplements and through the ingestion of contaminated water. Symptoms of phycotoxin intoxication include paralysis, diarrhea, and amnesia. When the cause of an intoxication cannot directly be found, a screening method is required to identify the causative toxin. In this work, such a screening method was developed and validated for marine and freshwater phycotoxins in different matrices: fish, shellfish, water, and food supplements. Two LC methods were developed: one for hydrophilic and one for lipophilic phycotoxins. Sample extracts were measured in full scan mode with an Orbitrap high resolution mass spectrometer. Additionally, a database was created to process the data. The method was successfully validated for most matrices, and in addition, regulated lipophilic phycotoxins, domoic acid, and some paralytic shellfish poisoning toxins could be quantified in shellfish. The method showed limitations for hydrophilic phycotoxins in sea water and for lipophilic phycotoxins in food supplements. The developed method is a screening method; in order to confirm suspected compounds, comparison with a standard or an additional analysis such as NMR is required.